1994
DOI: 10.1111/j.1476-5381.1994.tb17135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type A and B monoamine oxidase selective inhibition by Ro 41–1049 and Ro 19–6327 on dopamine outflow in rat kidney slices

Abstract: 1 The influence of pargyline and of selective inhibitors of type A and B monoamine oxidase (MAO), Ro 41-1049 and Ro 19-6327 respectively, on the outflow of dopamine and 3,4-dihydroxyphenylacetic acid (DOPAC) in slices of rat renal cortex loaded with exogenous L-3,4-dihydroxyphenylalanine (L-DOPA) was examined. Dopamine and DOPAC in the tissues and in the effluent were assayed by means of h.p.l.c. with electrochemical detection. 2 The levels of newly-formed dopamine and DOPAC in the perifusate decreased progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Altogether, the present data suggest that changes in renal dopamine production cannot be responsible for the increased fractional excretion of sodium in patients with impaired renal function and may instead favour sodium retention and thus increase blood pressure in these conditions. Previous studies provided evidence that in rat kidney newly formed dopamine is significantly inactivated, namely through deamination to DOPAC by MAO [6,10,12,18]. In addition, it has been shown that the human kidney is endowed with a greater activity of MAO than in the rat kidney [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, the present data suggest that changes in renal dopamine production cannot be responsible for the increased fractional excretion of sodium in patients with impaired renal function and may instead favour sodium retention and thus increase blood pressure in these conditions. Previous studies provided evidence that in rat kidney newly formed dopamine is significantly inactivated, namely through deamination to DOPAC by MAO [6,10,12,18]. In addition, it has been shown that the human kidney is endowed with a greater activity of MAO than in the rat kidney [19].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been gathered that at least 90% of urinary dopamine has its origin in the kidney [8] and the urinary levels of free dopamine are used as the main parameter for the assessment of dopamine formation in renal tissues [9]. However, it is well recognised now that under in vitro conditions newly formed dopamine in the rat and the human kidney undergoes extensive deamination to 3,4-dihydroxyphenylacetic acid (DOPAC), by monoamine oxidase (MAO) [6,[10][11][12]; a small amount of the amine is converted to homovanillic acid (HVA) by both MAO and catechol-Omethyltransferase (COMT) and a minor amount is methylated to 3-metoxytyramine (3-MT) [11]. Because daily urinary excretion of both DOPAC and HVA is several-fold that of the parent amine [13,14], these two amine metabolites may represent useful parameters for the assessment of renal dopaminergic system activity.…”
Section: Introductionmentioning
confidence: 99%
“…Urine concentrations of noradrenaline were quantified by means of HPLC with electrochemical detection, as previously described (Pestana and Soares-da-Silva, 1994). The lower limits of detection of noradrenaline ranged from 350 to 500 fmol.…”
Section: -H Urine Catecholamine Determinationmentioning
confidence: 99%
“…At the level of the proximal tubule, the overall increase in sodium excretion produced by dopamine results from the inhibition of two main sodium transport mechanisms at the basolateral and apical membranes, Na + ,K + -ATPase and Na + -H + exchanger, respectively [6]. Dopamine of renal origin has also been found to undergo extensive deamination to 3,4-dihydroxyphenylacetic acid (DOPAC), O -methylation to 3-methoxytyramine (3-MT) and deamination plus O -methylation to homovanillic acid (HVA) [7,8,9] and the high levels of metabolic enzymes such as type A and B monoamine oxidases (MAO-A and MAO-B) and catechol- O -methyltransferase (COMT) have also been considered important determinants in the overall availability of renal dopamine.…”
Section: Introductionmentioning
confidence: 99%